(untitled) (Medico Legal Update, 2021)
Utilization of vitamin AD3E during three periods of pregnancy for Friesian cows by injection and noninjection at the same periods was studied in different places in Shaqlawa technical institute farm and private local farms. (Vitamin and energy requirements are covered in their feed for all groups of treatments) Nine of female cows divided into three group’s three cows for each the control group (C) non-pregnancy and non-injection of vit AD3E, first group and the second group were pregnancies divided each of them in three treatments. The first group was non-injection but the second group was injection with vit.AD3E. Each of group first and second had three treatments treatment one (T1) first three months of pregnancy, treatment 2(T2) last three month of pregnancy and treatment three (T3) after two weeks of parturition. The results shows that was a significant increase (p?0.01) and best value observed for [White blood cell(WBC)/×10 9/L in G1T1(11.97), Red blood cell (RBC)/×10 12/L in G1T3(19.90), Packed cell volume (PCV)/Fl in G2T3 (43.22), Hemoglobin (HB)/g/Dl in G1T1(77.33), Mean size cell volume RBC (MCV)/Fl in G2T3(55.96), and Mean corpuscular Hemoglobin(MCH)/pg in G1T3(16.93)]. Its concluded from this results that vitamin AD3E of a (It can be concluded from this study that vit. AD3E have useful impact on blood parameters during pregnancy and after parturition due their high demands to these vitamins)